"Creativity of Alisher Navoi-The Pearl of Spirituality” - IBRAGIMOVNA, SHAKHNOZA NURMURADOVA (The journal of contemporary issues in business and government, 2021)
The article describes the talent, high creative potential of Alisher Navoi, the great representative of Turkish and Persian literature, in particular his role and services in the spiritual heritage of the Uzbek people. The memory of Alisher Navoi is highly respected in our country and the work carried out in this regard was mentioned. It is recognized that the great poet and thinker's work is an invaluable source not only of literature, but also of the treasure of the Uzbek language.